2019
DOI: 10.1002/admi.201901551
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Areal Density and Surface Passivation of ZnO Nanowire Array Enable Efficient PbS QDs Solar Cells with Enhanced Current Density

Abstract: Colloidal PbS quantum dots (QDs) have provoked a revolution in the field of optoelectronic devices owing to their low-cost fabrication processing and excellent physical properties. Recently, the fabrication of nanostructured PbS QDs photovoltaic (PV) devices based on zinc oxide (ZnO) nanowires array appeared as an effective strategy for improving the overall device performance. On This article is protected by copyright. All rights reserved. 2 the other hand, the infiltration of PbS QDs in a densely packed ZnO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…While a study published by Richters et al observed similar effects by in casing ZnO nanowires in Al 2 O 3 [6]. Recent work by Dastjerdi et al used hydrogen plasma to passivate surface states of ZnO nanowires and caused a reduction in defects observed with photoluminescence (PL) [7]. Other work carried out by Allen et al has shown that reactive oxygen species at the surface can influence the electrical properties and contact type [8,9].…”
Section: Introductionmentioning
confidence: 84%
“…While a study published by Richters et al observed similar effects by in casing ZnO nanowires in Al 2 O 3 [6]. Recent work by Dastjerdi et al used hydrogen plasma to passivate surface states of ZnO nanowires and caused a reduction in defects observed with photoluminescence (PL) [7]. Other work carried out by Allen et al has shown that reactive oxygen species at the surface can influence the electrical properties and contact type [8,9].…”
Section: Introductionmentioning
confidence: 84%
“…For effective light management in the IBHJ structures, too large or too small an area density leads to higher light reflectance, as shown in Figure 5 a, and an appropriate area density eventually leads to higher light absorption and higher J SC . Recently, Tavakoli Dastjerdi et al [ 93 ] obtained a champion device with a PCE of 10.1% by tuning the areal density of ZnO NWs (≈150 per μm 2 ) by controlling the precursor concentration. In short, the density control of NWs requires a balance between the interface area and the light trapping effect of NWs.…”
Section: Effect Of Zno Nanowire Morphology On the Scsmentioning
confidence: 99%
“…More recently, Tavakoli Dastjerdi et al [ 93 ] passivated ZnO NW surface states using the hydrogen plasma treatment. Compared with the untreated NWs, the PL spectrum of the H-plasma-treated ZnO NWs showed a clear enhancement of near-band emissions and a remarkable quenching of the visible emission peak.…”
Section: Optimization Strategies Of Ibhj Qdscs Based On Zno Nwsmentioning
confidence: 99%
“…Finding a suitable ETL in terms of mobility, band alignment and stability can improve the efficiency and stability of the device [27]. In PbS QDs PVs, ZnO is the commonly used materials for ETL, which normally shows a good PCE [22]. However, the loss‐in‐potential in PbS QDs PV is still remained a big challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extensive efforts have been devoted to this PV technology in order to further improve the device performance, resulting in a certified power conversion efficiency (PCE) of 12% [8][9][10][11][12]. There are couple of strategies for this purpose such as new ligand passivation approaches [13], architectural engineering [14][15][16], interface engineering [17][18][19][20], employment of nanostructured substrates [21,22], plasma and ultraviolet (UV) light treatments [13,22], employment of down-shifting materials [23][24][25] etc. Basically, in a QDs solar cell, the interface of PbS QDs layer/ electron transporting layer (ETL) plays a critical role in the device performance [26].…”
mentioning
confidence: 99%